Pemberdayaan Saung Belajar di Masa Pandemi Covid-19 terhadap Siswa SDN 2 Cikumpay - Pramudya, Firdaisya Adisti; Khotimatuzzahro, Siti; Wahab, Nugraha Bahtera; Octava, Widy Astuti; Ihyanudin, Fitri Latifah; Budiman, Ichsan (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2022)
The negative impact of online learning that is less than optimal will affect the level of student interest and level of understanding of students in the process of learning activities taking place. The problem of online learning that never ends is starting to reap the pros and cons among the community. This study aims to overcome the problems of online learning in SDN 2 Cikumpay, Cikumpay Village with various limitations. In this research method refers to the method of KKN DR Sisdamas (Community Based). Constraints in online learning such as weak signals and the absence of smartphones are the benchmarks in this study. This learning space empowerment activity is expected to be able to solve the obstacles that exist for students, teachers and the community regarding the government's policy to conduct online learning during the Covid-19 pandemic